EFIKASI-DIRI SISWA PADA MODEL SIKLUS BELAJAR 5E TERINTEGRASI PEER INSTRUCTION - Putri Dwi Sundari; Parno Parno; Sentot Kusairi (Graduate School of Universitas Negeri Malang, 2017)
Self-efficacy is an aspect of self-regulation that supports individual success. Teachers must design appropriate learning to improve students' self-efficacy. The purpose of this study is to analyze students' self-efficacy on 5E learning cycle model integrated peer instruction. Mixed-method research with embedded experimental design was conducted to 33 students. Research instrument is self-efficacy questionnaire with reliability 0,95. Quantitative data on self-efficacy was analyzed using paired t-test, while qualitative data was analyzed by reduction results of student interviews. Results showed that students' self-efficacy improved after learning. Students have confidence in linking physics concepts with other concepts of science, investigating, and using physics concepts in daily-life phenomena.Efikasi-diri merupakan aspek pengaturan-diri yang menunjang keberhasilan individu. Guru berperan merancang pembelajaran yang tepat untuk meningkatkan efikasi-diri siswa. Penelitian bertujuan menganalisis efikasi-diri siswa pada model siklus belajar 5E terintegrasi peer instruction. Penelitian mixed-method dengan desain embedded experimental ini melibatkan 33 siswa kelas X. Instrumen penelitian berupa angket efikasi-diri dengan reliabilitas 0,95. Data kuantitatif efikasi-diri dianalisis menggunakan paired t-test, sementara data kualitatif dianalisis dengan mereduksi hasil wawancara siswa. Hasil penelitian menunjukkan efikasi-diri siswa meningkat setelah pembelajaran. Siswa memiliki keyakinan dalam mengaitkan konsep fisika dengan konsep ilmu lainnya, melakukan investigasi, dan menggunakan konsep fisika pada fenomena di kehidupan sehari-hari.